2023
DOI: 10.1371/journal.pone.0281406
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coaching on physician wellness: A systematic review

Abstract: Physician wellness is critical for patient safety and quality of care. Coaching has been successfully and widely applied across many industries to enhance well-being but has only recently been considered for physicians. This review aimed to summarize the existing evidence on the effect of coaching by trained coaches on physician well-being, distress and burnout. MEDLINE, Embase, ERIC, PsycINFO and Web of Science were searched without language restrictions to December 21, 2022. Studies of any design were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Relevant characteristics of coaching interventions including publication details, study characteristics, occupational group, intervention, and outcome was extracted. Coaching is an evidence‐based intervention, 14 therefore, while outcome measures (e.g., effectiveness, feasibility, etc.) were extracted, they were not reported on, rather the focus lies with ‘type 3 evidence: implementation and context’ 33 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relevant characteristics of coaching interventions including publication details, study characteristics, occupational group, intervention, and outcome was extracted. Coaching is an evidence‐based intervention, 14 therefore, while outcome measures (e.g., effectiveness, feasibility, etc.) were extracted, they were not reported on, rather the focus lies with ‘type 3 evidence: implementation and context’ 33 .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, randomised-control trials 12 show the role of coaching to prevent exhaustion and emotional distress 13 as well as to promote self-efficacy and work-life balance. 14 In the Cleveland Clinic, peer-based coaching was associated with improved physician retention, yielding a potential cost saving of 133 million dollars. 15 Given its dual-benefits, coaching is increasingly being viewed as an important tool to, 'shift organisational culture with a new narrative around meaning and purpose', 16 broadly aligning with O'Connor & Cavangh's 17 'ripple effect'.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness is beneficial in increasing equanimity, for intra‐ and interpersonal skills and decreasing anxiety and perceived stress 1 . Coaching may be beneficial but needs further research 14 …”
Section: Organisation Issues That Contribute To Physician Well‐beingmentioning
confidence: 99%
“…A 2023 systematic review of studies including surgeons and non-surgeons, trainees and physicians in practice found that coaching for physicians was associated with an improvement in wellness and reduction in burnout. 7 Many of these studies utilized professional coaches, often from outside of health care, which can be cost-prohibitive. However, surgeons are able to learn to use coaching principles to engage in coaching interactions with both trainees and peers.…”
Section: Coaching During Training and Beyond Caprice C Greenberg (Cha...mentioning
confidence: 99%